Pengaruh Penggunaan Gawai Terhadap Minat Baca Siswa Kelas VIII UPTD SMP Negeri 10 Pematangsiantar - Rikki Daniel Hutasoit; Fentus Ruycosta Silalahi; Elisabeth Dwi Clara; Fienni Maranatha Situmorang; Desriani Tarigan; Chelsy Situmorang; Anton Luvi Siahaan (Young Journal of Social Sciences and Humanities, 2025)
Amid widespread public belief that digital devices symbolize educational progress, this study finds that these tools have instead become one of the most dominant factors contributing to the decline in reading interest among junior high school students. This research aims to analyze the influence of gadget-use intensity on the reading interest of eighth-grade students at UPTD SMP Negeri 10 Pematangsiantar using a quantitative approach. A total of 126 respondents participated through standardized questionnaires that had been tested for validity and reliability (Cronbach’s Alpha of 0.912 for the gadget-use intensity variable and 0.908 for reading interest). Data were analyzed using simple linear regression to examine the relationship and the magnitude of influence between variables. The results indicate a very strong negative relationship between gadget-use intensity and students’ reading interest (r = –0.942; p < 0.01), with an influence contribution of 88.7 percent. These findings affirm that uncontrolled gadget use significantly diminishes reading interest, particularly when digital entertainment content overshadows literacy activities. Nevertheless, gadgets cannot be entirely blamed; the negative effects arise from patterns of digital consumption that are not pedagogically guided. This study recommends enhanced parental supervision, school regulations, and the pedagogical integration of gadgets as learning tools so that technology functions as a literacy enhancer rather than a barrier.